20.6k views
2 votes
I need help understanding this

I need help understanding this-example-1
User RoyaumeIX
by
5.4k points

1 Answer

3 votes

Answer:

x = 6±sqrt( 31)

Explanation:

x^2 -12x +5 =0

Subtract 5 from each side

x^2 -12x +5-5=0-5

x^2 -12x = -5

Take the coefficient of x

-12

Divide by 2

-12/2 =-6

Square it

(-6 )^2 = 36

Add this to each side

x^2 -12x +36= -5+36

(x-6)^2 = 31

Take the square root of each side

sqrt((x-6)^2) =±sqrt( 31)

x-6 =±sqrt( 31)

Add 6 to each side

x-6+6 =6±sqrt( 31)

x = 6±sqrt( 31)

User Maleev
by
4.6k points